Evaluation of Structurally Different Ionic Liquid-Based Surfactants in a Green Microwave-Assisted Extraction for the Flavonoids Profile Determination of Mangifera sp. and Passiflora sp. Leaves from Canary Islands - Moučková, Kristýna; Pacheco-Fernández, Idaira; Ayala, Juan H.; Bajerová, Petra; Pino, Verónica (My University, 2020)
Aqueous solutions of ionic liquids (ILs) with surface active properties were used as extraction solvents, taking advantage of their impressive solvation properties, in a green microwave-assisted solid-liquid extraction method (IL-MA-SLE) for the extraction of flavonoids from passion fruit and mango leaves. The extraction method was combined with high-performance liquid chromatography and photodiode-array detection (HPLC-PDA) and optimized by response surface methodology using the Box-Behnken experimental design. Under optimum conditions, the extraction efficiency of six structurally different IL-based surfactants was evaluated. Thus, imidazolium-, guanidinium- and pyridinium-type ILs with different tailorable characteristics, such as side chain length and multicationic core, were assessed. The decylguanidinium chloride ([C10Gu+][Cl–]) IL-based surfactant was selected as key material given its superior performance and its low cytotoxicity, for the determination of flavonoids of several samples of Passiflora sp. and Mangifera sp. leaves from the Canary Islands, and using as target analytes: rutin, quercetin and apigenin. The analysis of 50 mg of plant material only required 525 µL of the low cytotoxic IL-based surfactant solution at 930 mM, 10.5 min of microwave irradiation at 30 °C and 50 W, which involves a simpler, faster, more efficient and greener method in comparison with other strategies reported in the literature for obtaining bioactive compounds profiles from plants.
Využití strukturně odlišných surfaktantů na bázi iontových kapalin pro mikrovlnnou extrakci flavonoidů z listů Mangifera sp. a Passiflora sp. pocházejících z Kanárských ostrovů
Keywords: ionic liquid-based surfactant; microwave-assisted extraction; mango; passion fruit; bioactive compounds; flavonoids; plant by-products; green extraction; surfaktanty na bázi iontových kapalin; mikrovlnná extrakce; mango; mučenka; bioaktivní sloučeniny; flavonoidy; vedlejší rostlinné produkty; zelená extrakce